Robotic radical cystectomy with concomitant implantation of 3-piece penile prosthesis: a one-step solution. (June 2021) - Izzo, Alessandro; Quarto, Giuseppe; Grimaldi, Giovanni; Castaldo, Luigi; Muscariello, Raffaele; Franzese, Dario; Del Prete, Paola; Ferro, Matteo; Barberio, Daniela; Bolognini, Ida; Bianchi, Attilio Antonio Montano; Autorino, Riccardo; et al.
Radical cystectomy (RC) remains a highly morbid urologic procedure, and erectile dysfunction (ED) represents a significant burden for bladder cancer survivors. While inflatable penile prosthesis (IPP) offers a definitive treatment option for post-RC ED, the hostile postoperative anatomy of RC patients poses some technical challenges for IPP implantation. We report the case of a 54-year-old male with high grade bladder cancer who was managed with a robotic-assisted RC with Bricker ileal conduit urinary diversion and simultaneous implantation of a 3-piece IPP. Operative time was 310 min (230 min for the RC and ileal conduit portion, 80 min for IPP implantation). Estimated blood loss was 300 ml. Postoperative course was regular. The patient was discharged home on postoperative day 6. A robotic RC with concomitant IPP implantation can be offered as "one-step" solution to bladder cancer male patients. This approach can potentially offer the advantage of better outcome in terms of sexual function, while minimizing surgical risks, ultimately improving the quality of life of these patients.